Does Gender Differentiate the Effects of Retirement on Cognitive Health?. (July 2019) - Oi, Katsuya
Prior research on change in cognitive performance before and after retirement suffers from inattention to gender context. This study theoretically motivates the testing of gender differences in cognitive decline after retirement. I drew 67, 905 observations of cognitive function based on the Telephone Interview for Cognitive Status from 18, 453 participants (7, 830 men and 10, 623 women) in the Health and Retirement Study (1992–2014). I used fixed-effects two-stage least square models to account for unobserved heterogeneity between men and women in the sample and the endogeneity of retirement decision. I also controlled for change in depressive symptoms, mobility limitations, individual wealth, medical expenses, and spousal income. Retirement predicts a decrease in the cognitive score by 2.168 on a scale of 0–35 for women, but no change for men. Continued employment may buffer against risk factors that aggravate women's cognitive health.